OPTIMALISASI EKSPERIMEN KERETA DINAMIKA: â€œAPLIKASI TRACKER VS TICKER TIMERâ€ UNTUK MENGURANGI MISKONSEPSI PADA MATERI GERAK LURUS BERUBAH BERATURAN (GLBB) - Elsa Anggiya Nurinsani; Nia Kurniasih; Nurdini Nurdini; Ating Herawati; Raden Giovanni Ariantara; Fitri Nurul Sholihat; Hana Susanti; Muhamad Gina Nugraha; Kartika Hajar Kirana (PROSIDING SEMINAR NASIONAL FISIKA (E-JOURNAL), 2017)
In the experiments, misconceptions can occur because of lack information or even incorrect information from the experiments performed. One of the experiments that are prone to misconceptions is a non uniform linear motion experiment. Generally, the misconceptions is the mass of objects affect for the acceleration of objects motion on the path of the sloping field. This research was conducted to compare the results of experimental data processing using two methods, that is using ticker timer and tracker application to determine more precise method, so it is expected to reduce the occurrence of misconception. This research was conducted by recording the dynamics of the mobility moves that change its mass using a high resolution camera with 24 frame / sec shooting speed. The data in the form of tape result of ticker timer in analysis using microcal origin software and video recording data were analyzed using tracker application. The result of data analysis shows that data processing using tracker produces more constant acceleration data compared with data from timer ticker band, so with application of tracker can be concluded there is no mass effect to acceleration motion of moving objects on sloping path. Utilization of tracker applications in the dynamics train experiment can be used as an alternative that can be used to reduce misconceptions on the teaching material of non uniform linear motion. Keywords: non uniform linear motion, tracker, misconception.